Clinical performance and patient outcome after simulation-based training in prevention and management of postpartum haemorrhage: an educational intervention study in a low-resource setting - Ellen Nelissen; Hege Ersdal; Estomih Mduma; Bjørg Evjen-Olsen; Jos Twisk; Jacqueline Broerse; Jos van Roosmalen; Jelle Stekelenburg (BMC, 2017)
Abstract Background Postpartum haemorrhage (PPH) is a major cause of maternal mortality. Prevention and adequate treatment are therefore important. However, most births in low-resource settings are not attended by skilled providers, and knowledge and skills of healthcare workers that are available are low. Simulation-based training effectively improves knowledge and simulated skills, but the effectiveness of training on clinical behaviour and patient outcome is not yet fully understood. The aim of this study was to assess the effect of obstetric simulation-based training on the incidence of PPH and clinical performance of basic delivery skills and management of PPH. Methods A prospective educational intervention study was performed in a rural referral hospital in Tanzania. Sixteen research assistants observed all births with a gestational age of more than 28 weeks from May 2011 to June 2013. In March 2012 a half-day obstetric simulation-based training in management of PPH was introduced. Observations before and after training were compared. The main outcome measures were incidence of PPH (500-1000 ml and >1000 ml), use and timing of administration of uterotonic drugs, removal of placenta by controlled cord traction, uterine massage, examination of the placenta, management of PPH (>500 ml), and maternal and neonatal mortality at 24 h. Results Three thousand six hundred twenty two births before and 5824 births after intervention were included. The incidence of PPH (500-1000 ml) significantly reduced from 2.1% to 1.3% after training (effect size Cohen's d = 0.07). The proportion of women that received oxytocin (87.8%), removal of placenta by controlled cord traction (96.5%), and uterine massage after birth (93.0%) significantly increased after training (to 91.7%, 98.8%, 99.0% respectively). The proportion of women who received oxytocin as part of management of PPH increased significantly (before training 43.0%, after training 61.2%). Other skills in management of PPH improved (uterine massage, examination of birth canal, bimanual uterine compression), but these were not statistically significant. Conclusions The introduction of obstetric simulation-based training was associated with a 38% reduction in incidence of PPH and improved clinical performance of basic delivery skills and management of PPH.